2011
DOI: 10.1103/physrevlett.106.047602
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ti3dCarriers in Mediating the Ferromagnetism ofCoTiO2Anatase Thin Films

Abstract: We study the surface and bulk electronic structure of the room-temperature ferromagnet Co:TiO2 anatase films using soft and hard x-ray photoemission spectroscopy with probe sensitivities of ∼1 nm and ∼10 nm, respectively. We obtain direct evidence of metallic Ti 3+ states in the bulk, which get suppressed to give a surface semiconductor, thus indicating a surface-bulk dichotomy. X-ray absorption and high-sensitivity resonant photoemission spectroscopy reveal Ti 3+ electrons at the Fermi level (EF ) and high-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Some studies that also claim the ferromagnetism of Co-doped TiO 2 is due to Co metal clusters [19][20][21][22]. The recent theoretical study by Calderon et al [23], electric fieldinduced anomalous Hall effect (AHE) study by Yamada et al [24] and x-ray photoemission spectroscopy study by Ohtsuki et al [25] suggested the ferromagnetism of Co-doped TiO 2 is due to carrier mediated. However, direct information about the magnetization as a function of carrier density has been lacking.…”
mentioning
confidence: 99%
“…Some studies that also claim the ferromagnetism of Co-doped TiO 2 is due to Co metal clusters [19][20][21][22]. The recent theoretical study by Calderon et al [23], electric fieldinduced anomalous Hall effect (AHE) study by Yamada et al [24] and x-ray photoemission spectroscopy study by Ohtsuki et al [25] suggested the ferromagnetism of Co-doped TiO 2 is due to carrier mediated. However, direct information about the magnetization as a function of carrier density has been lacking.…”
mentioning
confidence: 99%
“…However, second order processes, like resonant inelastic X-ray scattering (RIXS) and resonant photoemission (RPES), remain a major challenge for theory. For RPES, existing approaches are semiempirical [7][8][9][10], based on a well defined two-holes final state and on small clusters, and thus do not take into account the delocalization of intermediate states, the bandstructure of the system and multiple scattering effects in the propagation of photoelectrons.The huge experimental output from RPES on correlated materials [7,[11][12][13][14][15][16] and the intriguing quest for a determination of local magnetic properties put forward by pioneering experiments [14][15][16] call for advancements in the theoretical description of this spectroscopy. In experiments on CuO and Ni, it was shown that the RPES photocurrent with circular polarized light is spin polarized in antiferromagnets [14,15] and Curie paramagnets [16].…”
mentioning
confidence: 99%
“…The huge experimental output from RPES on correlated materials [7,[11][12][13][14][15][16] and the intriguing quest for a determination of local magnetic properties put forward by pioneering experiments [14][15][16] call for advancements in the theoretical description of this spectroscopy. In experiments on CuO and Ni, it was shown that the RPES photocurrent with circular polarized light is spin polarized in antiferromagnets [14,15] and Curie paramagnets [16].…”
mentioning
confidence: 99%
“…(La,Sr)MnO 3 showed a magnetic disorder on a surface, which was probably associated with a structural disorder [11]. In the case of (Ti,Co)O 2 , the magnetically dead layer was at least~5 nm thick [9] and could be attributed to a surface oxidation and/or a depletion layer due to the different surfaces and bulk electronic structures observed via soft and hard X-ray photoemission spectroscopy [12]. X-ray photoemission spectroscopy under ultraviolet illumination suggested that photoinduced carriers at a depleted layer intermediate exchange coupling between Co spins [13].…”
Section: Introductionmentioning
confidence: 91%